2013
DOI: 10.1371/journal.pone.0062452
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative Effect of Carvedilol and Aerobic Exercise Training Therapies on Improving Cardiac Contractility and Remodeling in Heart Failure Mice

Abstract: The use of β-blockers is mandatory for counteracting heart failure (HF)-induced chronic sympathetic hyperactivity, cardiac dysfunction and remodeling. Importantly, aerobic exercise training, an efficient nonpharmacological therapy to HF, also counteracts sympathetic hyperactivity in HF and improves exercise tolerance and cardiac contractility; the latter associated with changes in cardiac Ca2+ handling. This study was undertaken to test whether combined β–blocker and aerobic exercise training would integrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…In 5-7-month old α 2A /α 2Ca ARKO mice, it is possible to observe increased heart height, LV mass, cardiomyocyte width and CSA, as well as cardiac fibrosis and collagen volume, suggesting a phenotype generally observed in remodeled hearths 89,91,94,95,102 . In the study of Pereira et al 90 , quantitative morphometric analyses indicated that cardiomyocyte width and cardiac collagen were, respectively, 28% and 55% increased in α 2A /α 2Ca ARKO mice in comparison with age-matched control 90 .…”
Section: Exercise Training and Cardiovascular Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…In 5-7-month old α 2A /α 2Ca ARKO mice, it is possible to observe increased heart height, LV mass, cardiomyocyte width and CSA, as well as cardiac fibrosis and collagen volume, suggesting a phenotype generally observed in remodeled hearths 89,91,94,95,102 . In the study of Pereira et al 90 , quantitative morphometric analyses indicated that cardiomyocyte width and cardiac collagen were, respectively, 28% and 55% increased in α 2A /α 2Ca ARKO mice in comparison with age-matched control 90 .…”
Section: Exercise Training and Cardiovascular Diseasesmentioning
confidence: 98%
“…This phenotype is not well established in 3-month old α 2A /α 2Ca ARKO mice 90,92,102 . However, from the 5 th month of life, these animals present suggestible muscle profile of skeletal myopathy due to decreased motor performance (i.e., Rotard test), increased oxidative stress (i.e., lipid hydroperoxidation and protein carbonylation), gastrocnemius capillary rarefaction, muscle atrophy of type I and type II fibers and, due to all these factors, exercise intolerance 89,91,93,95,101,102 .…”
Section: Heart Failurementioning
confidence: 99%
“…Low intensity exercise training has been shown to delay the onset of heart failure in the spontaneously hypertensive heart failure rat without effects on hypertension (Emter et al, 2005). Training also improved cardiac function in surgical and genetic models of heart failure or hypertrophic cardiomyopathy in mice (Konhilas et al, 2006; McMullen et al, 2007; Vanzelli et al, 2013). In humans, the largest study to examine the effects of exercise in heart failure patients was the HF-ACTION trial that examined the safety and efficacy of exercise in over 2300 patients with heart failure with reduced ejection fraction (HFrEF) (O'Connor et al, 2009).…”
Section: Translational and Therapeutic Implicationsmentioning
confidence: 99%
“…Moderate exercise training delays cardiac dysfunction and prevents calcium handling abnormalities in sympathetic hyperactivity-induced heart failure mice (Medeiros et al, 2008;Oliveira et al, 2009;Vanzelli et al, 2013). Kavazis and co-workers have recently shown that short-term exercise training protects the heart against doxorubicin-induced heart failure by preventing cardiac mitochondrial dysfunction and increased oxidant stress .…”
Section: Heart Failurementioning
confidence: 99%